Hi Dalia:
A_{n} = 2 + 5*(n-1), where n= 1, 2, 3, ...
The first term occurs when n=1:
A_{1} = 2 + 5(1-1) = 2
The other terms work the same way, just plug in the different values of n (n = 2, 3, 4, 5).
The common difference is just the difference between one term and the next one after it. To compute it, do the following subtraction:
Common Difference = A_{n+1} - A_{n}
where
A_{n+1} = 2 + 5((n+1) - 1) = 5n + 2
A_{n} = 2 + 5(n-1) = 2 + 5n - 5 = 5n - 3
Subtract A_{n} from A_{n+1} to get the answer. Let me know what you get in the comments and I'll let you if it's right.